The Effects of Uncomplicated Cataract Surgery on Retinal Layer Thickness - Ali Kurt; Raşit Kılıç (Journal of Ophthalmology)
Purpose. Our aim was to assess changes in the total retinal thickness (TRT), total retinal volume (TRV), and retinal layer thickness after uncomplicated cataract surgery. Methods. A total of 32 eyes of 32 patients who had undergone uncomplicated phacoemulsification surgery and intraocular lens implantation in one eye were enrolled. Effective phacoemulsification time (EPT) and total energy (TE) were recorded. Thickness and TRV were measured using optical coherence tomography. Data were collected preoperatively and at postoperative day 1, 7, 30, 90, and 180. Results. The study results showed a decrease in TRT, TRV, and most retinal layer thicknesses at the first postoperative day visit and then increasing at week 1, and months 1 and 3, and then relatively decreasing at month 6 although not returning to preoperative levels. The least affected layers were the retinal pigment epithelium and outer plexiform layer. There was a positive correlation between EPT and TE and ganglion cell layer in a 1 mm circle and inner nuclear layer in a 1–3 mm circle (p<0.05). Conclusion. The results suggest that long-term follow-up of more than 6 months is necessary after cataract surgery to see whether total retinal and segmental values return to preoperative levels. This study was registered with Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12618000763246.